Serum Zonula Occludens-1 and Claudin-5 Levels in Patients with Insomnia Disorder: A Pilot Study - Fan M; Deng F; Tang R; Cai Y; Zhang X; Li H; Xiang T; Pan J (Nature and Science of Sleep, 2023)
Mei Fan, Fangyi Deng, Rui Tang, Yixian Cai, Xiaotao Zhang, Hongyao Li, Ting Xiang, Jiyang Pan Department of Psychiatry, Sleep Medicine Centre, The First Affiliated Hospital, Jinan University, Guangzhou, People’s Republic of ChinaCorrespondence: Jiyang Pan, Department of Psychiatry, Sleep Medicine Centre, The First Affiliated Hospital, Jinan University, 613, West Huangpu Avenue, Guangzhou, 510630, People’s Republic of China, Tel +86 2038688651, Email jiypan@vip.163.comPurpose: This research aimed to investigate serum Zonula occludens-1 (ZO-1) and Claudin-5 (CLDN5) levels to show whether or not their eventual changes in patients with insomnia disorder could have etiopathogenetic importance. There was no research investigating serum ZO-1 and CLDN5 concentrations in insomnia disorder.Patients and Methods: This study included 60 insomnia disorder patients and 45 normal controls. None of the patients received drugs for insomnia. The patients completed Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI), and Polysomnography (PSG) to score the insomnia disorder symptoms. Venous blood samples were collected, and serum ZO-1 and claudin-5 levels were analyzed by enzyme-linked immunosorbent assay (ELISA).Results: Serum ZO-1 level was significantly higher without a significant difference between age, sex, and body mass index, whereas the difference in serum claudin-5 level between the two groups was not statistically significant. In addition, ZO-1 levels were positively correlated with ISI and PSQI and negatively with N1 and N1_perc. We also demonstrated a positive correlation between the levels of CLDN5 and HAMA, and a negative correlation with total sleep time (TST), N1 and N1_perc.Conclusion: Our findings suggest an association between these intestinal and brain endothelial permeability markers and insomnia disorders. However, these remain modest and preliminary and need more extensive studies, including long-term follow-up populations and involving gut microbes, to further validate and explore the mechanisms involved.Keywords: insomnia disorder, blood-brain barrier, intestinal permeability, claudin-5, zonula occludens-1, biomarker